Bernardino Ramazzini and William Osler, two paternities - Piscoya-Arbañil, Julio Alberto (2020)
This article highlights the development and contribution, based on bibliographic sources, of two personalities in Medicine, Dr. Bernardino Ramazzini and Dr. William Osler; the first with his contributions in the field of Occupational Medicine, occupational health and occupational epidemiology, publishing the first treatise on occupational diseases, “De Morbis Artificum Diatriba” and the second, an internist with his special disposition and concern for teaching and research and publication of his famous book “ “The Principles and Practice of Medicine” that was the basis of the publications for the medical schools of the world today and that had worldwide significance. Its achievements are discussed, finally establishing a parallel in these outstanding doctors who are recognized by history as the father of Occupational Medicine and the Father of Modern Medicine